(untitled) - Prabwo, Dibyo (Rome, 1993)
The primary objective of this document is to report the results of a study was undertaken in early 1988 to identify and, where possible, quantify the changes that had occurred in the farming systems of selected villages in Central Java during the 14-year period from 1974 to 1988. An attempt has also been made to identify the reasons why changes have occurred or which constraints have prevented changes from occurring, with a view to separating predictable responses from unpredictable changes. The study was undertaken in order to provide material for use in workshop on farm-household systems analysis.
Keywords: farm management